Development of Electronic Medical Record-Based "Rounds Report" Results in Improved Resident Efficiency, More Time for Direct Patient Care and Education, and Less Resident Duty Hour Violations. Issue 9 (September 2016) - Ham, Phillip B.; Anderton, Toby; Gallaher, Ryan; Hyrman, Mike; Simmerman, Erika; Ramanathan, Annamalai; Fallaw, David; Holsten, Steven; Howell, Charles Gordon
Surgeons frequently report frustration and loss of efficiency with electronic medical record (EMR) systems. Together, surgery residents and a programmer at Augusta University created a rounds report (RR) summarizing 24 hours of vitals, intake/output, labs, and other values for each inpatient that were previously transcribed by hand. The objective of this study was to evaluate the RR's effect on surgery residents. Surgery residents were queried to assess the RR's impact. Outcome measures were time spent preparing for rounds, direct patient care time, educational activity time, rates of incorrect/incomplete data on rounds, and rate of duty hour violations. Hospital wide, 17, 200 RRs were generated in the 1-month study. Twenty-three surgery residents participated. Time spent preparing for rounds decreased per floor patient (15.6 ± 3.0 vs 6.0 ± 1.2, P < 0.0001) and per intensive care unit patient (19.9 ± 2.9 vs 7.5 ± 1.2 P < 0.0001). The work day spent in direct patient care increased from 45.1 ± 5.6 to 54.0 ± 5.7 per cent ( P = 0.0044). Educational activity time increased from 35.2 ± 5.4 to 54.7 ± 7.1 minutes per resident per day ( P = 0.0004). Reported duty hour violations decreased 58 per cent ( P < 0.0001). American Board of Surgery in Training exam scores trended up, and estimates of departmental annual financial savings range from $66, 598 to $273, 141 per year. Significant improvements occur with surgeon designed EMR tools like the RR. Hospitals and EMR companies should pair interested surgeons with health information technology developers to facilitate EMR enhancements. Improvements like RRs can have broad ranging, multidisciplinary impact and should be standard in all EMRs used for inpatient care at academic medical centers.